Evaluation of facial soft tissue parameters for Palestinians using Holdaway analysis - Emad Hussein; Susan Al Khateeb; Nezar Watted; Alev Aksoy; Ahu Acar; Mahmoud Abu Mowais (Saudi Dental Journal)
Objective: The aims of this study were to evaluate soft-tissue measurements for a Palestinian sample population with normal occlusion by Holdaway’s analysis, and to check the applicability of Holdaway values to the Palestinian population. Normal Holdaway values for Palestinians will be established if their parameters do not match those of Holdaway. Material and methods: Cephalometric radiographs of 93 Palestinian university students with normal occlusion (63 women, mean age: 20.1 ± 2.1 years; 30 men, mean age: 20.2 ± 2.4 years) were traced and evaluated. Cephalometric landmarks were located according to Holdaway analysis. Ten linear and two angular measurements were produced on each radiograph. Results: The soft-tissue measurements for the Palestinians were similar to the Holdaway norms, except for the soft-tissue convexity angle and soft-tissue chin thickness, which were larger than the Holdaway averages. The Palestinian sample had a narrower range for normal nose prominence, as well as thicker lips, deeper superior and inferior sulci, and thicker soft-tissue chins than the Holdaway values. Conclusions: We determined normal values for the Holdaway soft-tissue analysis for Palestinians, which are appropriate for use in orthodontic practices in these territories. Keywords: Soft tissue, Cephalometric norms, Holdaway analysis